PENGARUH PENYULUHAN DENGAN METODE CERAMAH DAN DISKUSI TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP ANAK TENTANG PHBS DI SEKOLAH DASAR NEGERI 065014 KELURAHAN NAMOGAJAH KECAMATAN MEDAN TUNTUNGAN TAHUN 2013 - zul salasa; Namora Lumongga; Eddy Syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACK Clean and healthy behavior (PHBS) in schools is a set of behaviors practiced by learners, teachers and schools on the basis of the society awareness of learning outcomes, thus independently capable of preventing disease, improving health, and plays an active role in creating a healthy environment. One effort that can be done to improve the knowledge and attitudes of children of PHBS is through health education by providing counseling PHBS. This study aims to determine the influence of illumination with a lecture and discussion to improve the knowledge and attitudes of children about PHBS in SDN 065014 Namogajah sub-district Medan Tuntungan. This research was a quasi-experimental design with one group pre-test and post-test. The study population was grade 4 and 5 students who attend school on SDN 065014 in the academic year 2012/2013, amounting to 38 people, 19 people to a group of 19 people for lectures and group discussion method. Data obtained from the questionnaire questions. Test used paired sample t-test and independent sample t-test. The results showed that the average value of the highest knowledge in the group discussion method than the lecture method at 22.47 with t count -2.651 and (p) 0.012. While the attitude of the highest in the group discussion method was also at 14.00 with t count -3.750 and (p) 0.001. The test results independent sample t-test showed the method of discussion is more effective in improving knowledge and attitudes of children about PHBS in SDN 065 014. It is recommended to teachers and health clinic staff to prioritize discussion method as an alternative to the provision of information to improve the knowledge and attitudes of children of PHBs on SDN 065 014.